1996
DOI: 10.1103/physrevb.53.14359
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental observation of guided polarized neutrons in magnetic-thin-film waveguides

Abstract: Guided propagation of polarized neutrons has been observed directly in magnetic CoZr/Al/CoZr trilayer deposited on Gd 3 Ga 5 O 12 garnet substrate by using neutron reflectometry technique. The resonance observed in the transmission spectrum of neutrons corresponding to two low order guided modes is in good agreement with theoretical predictions. A detailed theoretical description of the guided propagation in thin-film neutron waveguides is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…The theory of neutron channeling was developed in [16]. Experimentally, the phenomenon of neutron channeling was observed in [8,17,18] and the channelling length was measured experimentally in [19,20]. It has also been demonstrated that it may be used for production of unpolarised [21] and polarised [22,23] neutron microbeams, which was used for the investigation of amorphous magnetic wires [24,25].…”
mentioning
confidence: 99%
“…The theory of neutron channeling was developed in [16]. Experimentally, the phenomenon of neutron channeling was observed in [8,17,18] and the channelling length was measured experimentally in [19,20]. It has also been demonstrated that it may be used for production of unpolarised [21] and polarised [22,23] neutron microbeams, which was used for the investigation of amorphous magnetic wires [24,25].…”
mentioning
confidence: 99%
“…Neutron reflectivity curves on the films doped with benzene-d 6 were obtained on the EROS time-of-flight reflectometer (Saclay, France) described in detail elsewhere (Pogossian & Menelle, 1996). Measurements were performed on the horizontal samples at the incident angles of 1.1 0 using a beam of 1 mm in height and 20 mm in width.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in 1994, Feng et al experimentally demonstrated confined propagation of modes for slow neutrons in thin titanium films [8]. For further significant works on confined thermal neutron propagation in thin planar waveguides, also in the framework of neutron optics, see the other references in [8][9][10][11][12][13][14]. Other important studies are those of Kumakhov et al [15] and Chen et al [16], both in 1992, establishing experimentally the focusing of slow neutrons by using polycapillary glass fibre.…”
Section: Formulation Of the Problemmentioning
confidence: 99%